Legal Protection of Children's Rights in Indonesia's Labor System - Saptaji, Aji; Jaenudin, Jaenudin; Rofi'atun Nisa, Rasyida (CIC Lembaga Riset dan Konsultan Sosial, 2024)
Children have fundamental rights that must be fulfilled by parents and guaranteed by the state. These rights are even mandated by the United Nations (UN) as part of efforts to protect children. This research raises the issue of protecting the rights of children who are employed underage, especially in the context of regulations that are still not entirely clear regarding child labor. This issue is important because children who work underage often face violations of fundamental rights, exploitation, and lack of access to education and social protection. This research is normative with a legislative approach and legal concept analysis. The research data source uses library materials, which include the 1945 Constitution, Law Number 13 of 2003 concerning Labour, ILO Conventions, and Law Number 35 of 2014 concerning Child Protection. The study was conducted by analyzing laws and regulations related to child labor, identifying the weaknesses of existing rules, and providing legal analysis based on applicable legal concepts. The results show that although there is a legal basis governing child labor, its implementation and supervision are still weak. There is a need for more stringent regulatory updates and increased synergy between relevant agencies to ensure the protection of the rights of children working underage. In addition, a holistic approach is needed to prioritize children's rights, including education, health, and social security, to create an environment free from child exploitation.